Dynamic migration of γδ intraepithelial lymphocytes requires occludin - Edelblum, Karen L. (National Academy of Sciences, 2012)
γδ intraepithelial lymphocytes (IELs) are located beneath or between adjacent intestinal epithelial cells and are thought to contribute to homeostasis and disease pathogenesis. Using in vivo microscopy to image jejunal mucosa of GFP γδ T-cell transgenic mice, we discovered that γδ IELs migrate actively within the intraepithelial compartment and into the lamina propria. As a result, each γδ IEL contacts multiple epithelial cells. Occludin is concentrated at sites of γδ IEL/epithelial interaction, where it forms a ring surrounding the γδ IEL. In vitro analyses showed that occludin is expressed by epithelial and γδ T cells and that occludin derived from both cell types contributes to these rings and to γδ IEL migration within epithelial monolayers. In vivo TNF administration, which results in epithelial occludin endocytosis, reduces γδ IEL migration. Further in vivo analyses demonstrated that occludin KO γδ T cells are defective in both initial accumulation and migration within the intraepithelial compartment. These data challenge the paradigm that γδ IELs are stationary in the intestinal epithelium and demonstrate that γδ IELs migrate dynamically to make extensive contacts with epithelial cells. The identification of occludin as an essential factor in γδ IEL migration provides insight into the molecular regulation of γδ IEL/epithelial interactions.